2020
DOI: 10.17159/2413-3221/2020/v48n2a540
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting subsistence farming in rural areas of nyandeni local municipality in the Eastern Cape Province

Abstract: Agriculture is the foremost locomotive of the economic growth for Sub-Saharan African countries, especially South Africa. Subsistence agriculture is one of the imperative segments in the South African economy and it remains a substantial sector for livelihood generation. Agricultural activities have an ability to provide nutrition, economic, social status and reduce rural poverty. However, subsistence farming has experience significant declined over the past 10 years due to climate change, scarcity of resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The finding further revealed that 30.1% of the participants had household size of 7 to 9 and 9.2% had 10 persons within the household. However, there is possibility for increase agricultural production in larger household size if a farmer uses family labour in agricultural activities (Siphesihle and Lelethu, 2020). Most households in South Africa, relies on agriculture for employment, food supplies and income generation (Chotonge (2013).…”
Section: The Socio-economic Characteristics Of Respondentsmentioning
confidence: 99%
“…The finding further revealed that 30.1% of the participants had household size of 7 to 9 and 9.2% had 10 persons within the household. However, there is possibility for increase agricultural production in larger household size if a farmer uses family labour in agricultural activities (Siphesihle and Lelethu, 2020). Most households in South Africa, relies on agriculture for employment, food supplies and income generation (Chotonge (2013).…”
Section: The Socio-economic Characteristics Of Respondentsmentioning
confidence: 99%
“…Family size bears an influence on the amount of food consumed by the family. Thus, there is higher likelihood that households with more family members would involve in subsistence agriculture in order to ensure food security (Siphesihle and Lelethu, 2020). In this study, family sizes are comparatively similar among the two population groups (Semi-settled = 6.8, Settled = 6.3, p value = 0.37).…”
Section: Agriculture For Income Generationmentioning
confidence: 55%
“…Agriculture is an integral source of food production and it plays a vital role in both local as well as global economic development [1][2][3] . For instance, it is evidenced from many of the studies [4][5][6][7] , that the majority of the dwellers in rural areas derive their livelihoods from agricultural activities in Nigeria. Besides, it is intrinsically aware that the farmers have ever since the existence of mankind been the soul of nations, particularly in terms of food supply to the masses.…”
Section: Introductionmentioning
confidence: 99%